2004
DOI: 10.1203/01.pdr.0000115681.95957.d4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Responses in the Fetal Sheep Brain to Low-Dose Endotoxin

Abstract: Clinical and experimental evidence indicate that infection in pregnancy is associated with fetal brain damage. However, the inflammatory processes that compromise the fetal brain are not fully understood. In this study, we used a single, low dose of lipopolysaccharide (LPS, 0.1 g/kg i.v.) to provoke an acutephase response in unanesthetized fetal sheep in utero. COX-2 mRNA was increased in the cortex and cerebellum at 24 and 48 h after LPS, and immunoreactive COX-2 protein was increased in perivascular cells th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 46 publications
2
49
0
1
Order By: Relevance
“…Within the UCO fetal brains, intense albumin staining was notable in the parenchyma adjacent to blood vessels, indicative of increased blood vessel permeability (fig. 2e) [30]. We quantified the number of albumin-positive vessels and found that UCO induced a significant increase within the thalamus (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Within the UCO fetal brains, intense albumin staining was notable in the parenchyma adjacent to blood vessels, indicative of increased blood vessel permeability (fig. 2e) [30]. We quantified the number of albumin-positive vessels and found that UCO induced a significant increase within the thalamus (fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the fetal sheep, Yan and colleagues have demonstrated that blood-brain barrier permeability is increased in the fetal brain after exposure to endotoxin, suggesting that cytotoxic and pro-inflammatory substances can pass from the circulation into the brain after peripheral inflammatory stimulation [31] . LPS has been associated with marked mitochondrial dysfunction after local injection in the striatum of adult rats [32] , and peripheral injection in adult mice [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive resuscitative procedures at delivery improve circulation and blood pressure that could eventually result in early P/IVH as a reperfusion injury. Secondly, external stimuli, including endotoxin, as well as cytokines and hypoxia, could directly affect immature vessels of the germinal matrix, increase blood-brain barrier permeability [32] and destroy their integrity [33] . Exposure to fl uctuating CBF could eventually result in hemorrhage within this region.…”
Section: Discussionmentioning
confidence: 99%